Solve for p -3p+6=-2

Math
-3p+6=-2
Move all terms not containing p to the right side of the equation.
Tap for more steps…
Subtract 6 from both sides of the equation.
-3p=-2-6
Subtract 6 from -2.
-3p=-8
-3p=-8
Divide each term by -3 and simplify.
Tap for more steps…
Divide each term in -3p=-8 by -3.
-3p-3=-8-3
Cancel the common factor of -3.
Tap for more steps…
Cancel the common factor.
-3p-3=-8-3
Divide p by 1.
p=-8-3
p=-8-3
Dividing two negative values results in a positive value.
p=83
p=83
The result can be shown in multiple forms.
Exact Form:
p=83
Decimal Form:
p=2.6‾
Mixed Number Form:
p=223
Solve for p -3p+6=-2

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top